Cognitive activity significantly affects the dynamic cerebral autoregulation, but not the dynamic vasoreactivity, in healthy adults - Rizko, Jasmin M.; Beishon, Lucy C.; Panerai, Ronney B.; Marmarelis, Vasilis Z. (Frontiers in Physiology, 2024)
Neurovascular coupling (NVC) is an important mechanism for the regulation of cerebral perfusion during intensive cognitive activity. Thus, it should be examined in terms of its effects on the regulation dynamics of cerebral perfusion and its possible alterations during cognitive impairment. The dynamic dependence of continuous changes in cerebral blood velocity (CBv), which can be measured noninvasively using transcranial Doppler, upon fluctuations in arterial blood pressure (ABP) and CO2 tension, using end-tidal CO2 (EtCO2) as a proxy, can be quantified via data-based dynamic modeling to yield insights into two key regulatory mechanisms: the dynamic cerebral autoregulation (dCA) and dynamic vasomotor reactivity (DVR), respectively. Using the Laguerre Expansion Technique (LET), this study extracted such models from data in supine resting vs. cognitively active conditions (during attention, fluency, and memory tasks from the Addenbrooke's Cognitive Examination III, ACE-III) to elucidate possible changes in dCA and DVR due to cognitive stimulation of NVC. Healthy volunteers (n=39) were recruited at the University of Leicester and continuous measurements of CBv, ABP, and EtCO2 were recorded. Modeling analysis of the dynamic ABP-to-CBv and CO2-to-CBv relationships showed significant changes in dCA, but not DVR, under cognitively active conditions compared to resting state. Interpretation of these changes through Principal Dynamic Mode (PDM) analysis is discussed in terms of possible associations between stronger NVC stimulation during cognitive tasks and enhanced sympathetic activation.